Skrifbeskouing en Skrifhantering: Marcus Borg en die Hervormde Kerk – ŉ Vergelykende studie - Eck, Ernest van (2017)
Marcus Borg, one of the most prominent New Testament scholars in the past four decades, is considered by many in the Netherdutch Reformed Church of Africa as a liberal scholar. His understanding of the origin of the Bible, the way he interprets the Bible, and what he sees as the status and function of the Bible, should therefore be dismissed. A comparison of Borg’s point of view on these topics with that of the points of view of the Netherdutch Reformed Church of Africa, however, indicates that Borg’s understanding of these matters differs not even marginally from that of the Netherdutch Reformed Church of Africa. In a certain sense, Borg could therefore be described as a theologian who fits the mould of what is understood in the Netherdutch Reformed Church of Africa as a responsible approach to and interpretation of the Bible.
Keywords: Interpretation; Netherdutch Reformed Church; Biblical Hermeneutics; Marcus Borg